2010
DOI: 10.1007/s10654-010-9517-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between domains of physical activity and all-cause, cardiovascular and cancer mortality

Abstract: International audienceFew studies have investigated the independent effects of domain-specific physical activity on mortality. We sought to investigate the association of physical activity performed in different domains of daily living on all-cause, cardiovascular (CVD) and cancer mortality. Using a prospective cohort design, 4,672 men and women, aged 25-74 years, who participated in the baseline examination of the MONICA/KORA Augsburg Survey 1989/1990 were classified according to their activity level (no, lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
125
3
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(152 citation statements)
references
References 32 publications
13
125
3
11
Order By: Relevance
“…Analyses of the association between work-related physical activity and mortality provided conflicting results. They range from a protective effect (Autenrieth et al, 2011;Barengo et al, 2004;Samitz et al, 2011) to no effects (Besson et al, 2008) (in line with our results) to deleterious effects, at least in men (Herzig et al, 2012). Null findings between occupational physical activity and mortality may be due to residual confounding or the broad physical activity categorisation due to job type only.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Analyses of the association between work-related physical activity and mortality provided conflicting results. They range from a protective effect (Autenrieth et al, 2011;Barengo et al, 2004;Samitz et al, 2011) to no effects (Besson et al, 2008) (in line with our results) to deleterious effects, at least in men (Herzig et al, 2012). Null findings between occupational physical activity and mortality may be due to residual confounding or the broad physical activity categorisation due to job type only.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, some effects were as strong as or even stronger for cancer mortality than for CVD mortality, as has been reported in other studies, e.g. In line with (Autenrieth et al, 2011;Besson et al, 2008) and in contrast to (Andersen et al, 2000;Samitz et al, 2011) others, we found no significant association between walking or cycling to work and all-cause mortality. This inconsistency may be explained by country-specific physical environments present for active commuting or by different measurement instruments.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations